EVALUASI PROGRAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Jaelani, Ahmad; Asvio, Nova (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research aimed at (1) evaluating the achievement of character education programs at the primary school level; (2) provide recommendations to both teachers, schools, and the government to improve character education programs. The method used is program evaluation (formative evaluation) with a qualitative approach. Research subjects at SDN 22 Rimau Island Data were analyzed using Milles & Huberman data analysis including; data reduction, data presentation, and data verification. The conclusion of this study is; (1) readiness of primary schools in SDN 22 Pulau Rimau to implement character education, both assessed from curricula that have integrated character education, but are still lacking in the management of supporting infrastructure; (2) the implementation of character education has not been seen in learning activities; (3) support from the government to socialize or provide training is felt to be lacking by schools; (4) monitoring and evaluation of character education is still limited to the curriculum and carried out through supervision of supervisors in each school; and (5) constraints faced by schools are the assessment of undocumented student attitudes, teachers lack understanding to implement character education, and the absence of synergy between education in schools and education at home.